Nanosized alkaline earth metal titanates: effects of size on photocatalytic and dielectric properties - Demydov, Dmytro V. (Kansas State University, 2006)
A new approach to synthesize nanosized strontium titanate (SrTiO3) and barium titanate (BaTiO3) has been developed. Nanocrystals of mixed metal oxide were synthesized by a modified aerogel procedure from alkoxides. The textural and surface characteristic properties were studied by nitrogen BET analysis, transmission electron microscopy, and powder XRD. The crystallite sizes of aerogel prepared powders can vary from 6 to 25 nm by the use of different solvents. A mixture of ethanol and toluene was found to be the best binary solvent for supercritical drying, which produced a SrTiO3 sample with a surface area of 159 m2/g and an average crystallite size of 8 nm, and a BaTiO3 sample with a surface area of 175 m2/g and an average crystallite size of 6 nm. These titanates have been studied for photocatalytic oxidation of volatile organic compounds and acetaldehyde (CH3CHO) in particular. The big band gaps of the bulk (3.2 eV for SrTiO3 and 3.1 eV for BaTiO3) limit their application to a UV light region only. The modification of titanates by doping with transition metal ions (partial substitution of Ti ions with metal ions) creates a valence band or electron donor level inside of the band gap, narrows it, and increases the visible light absorption. The enhanced adsorption of visible light was achieved by the synthesis of nanosized SrTiO3 and BaTiO3 by incorporating Cr ions during the modified aerogel procedure. Gaseous acetaldehyde photooxidation has been studied on pure SrTiO3 and BaTiO3, and on chromium doped Cr-SrTiO3 and Cr-BaTiO3 under UV and visible light irradiation, and compared with the photoactivity of P25 TiO2. SrTiO3 doped with antimony/chromium shows absorption in visible light and show photocatalytic activity for CH3CHO oxidation. The reason for the codoping of SrTiO3 with Sb/Cr was to maintain the charge balance and to suppress oxygen defects in the lattice. This photocatalyst shows high photoactivity under visible light irradiation even after several continuous runs. The photoactivity under visible and UV light irradiation was almost identical for the Sb/Cr-SrTiO3 photocatalyst. Dielectric properties of aerogel prepared barium titanate samples have being studied and the bulk resistance values of AP-BaTiO3 were significantly lower than that of commercial BaTiO3, by several orders of magnitude.
Keywords: aerogel; nanosized; strontium titanate; barium titanate; Chemistry, Inorganic (0488)